2019
DOI: 10.4103/jpbs.jpbs_26_19
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between benign and metastatic cervical lymph nodes using ultrasound

Abstract: Purpose: The oral cavity is the most common site for squamous cell carcinoma, which has a distinct predilection for lymphatic spread before distant systemic metastasis. The cervical lymph node status is a very important consideration in the assessment of squamous cell carcinoma. Ultrasound is a noninvasive and inexpensive technique that can be used to differentiate between the benign and metastatic nodes. So the aim of this study was to evaluate reliability of ultrasound for such differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that the normal and reactive lymph nodes are oval, while the malignant and tuberculous lymph nodes are round ( 1 ). A different study found that the cervical lymph nodes are oval in all oral squamous cell carcinoma cases ( 5 ). In the present study, the shape of the submandibular and submental lymph nodes was mostly oval in both healthy and odontogenic infected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the normal and reactive lymph nodes are oval, while the malignant and tuberculous lymph nodes are round ( 1 ). A different study found that the cervical lymph nodes are oval in all oral squamous cell carcinoma cases ( 5 ). In the present study, the shape of the submandibular and submental lymph nodes was mostly oval in both healthy and odontogenic infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the normal cervical lymph nodes is under 0.5, the ratio of a tuberculous lymph nodes is greater than 0.5, and the ratio of the lymph nodes with odontogenic infection is 0.47 ( 1 , 14 ). A rate 0.67 and above confirms a metastatic lymph node with a probability of 70.44% ( 5 ). In the present study, the mean ratio of the right and left submandibular lymph nodes with odontogenic infection were 0.55 and 0.60, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Size, shape, echogenicity, echogenic hilum, internal echo, necrosis, margin, vascular pattern, elastography, and grouping or matting are reported to be US features associated with malignant nodal disease. 16 18 , 41 46 The accuracy of differentiation between benign and malignant LN varies according to nodal size and the optimal cutoff differs at different neck levels. 42 , 43 , 47 Shape is usually described in terms of the ratio between the short-axis and long-axis diameters (S/L ratio).…”
Section: Pretreatment and Surgical Phasementioning
confidence: 99%
“…It is important to note that while some US features are promising in identifying LN metastases, a single US feature cannot predict a malignant LN 1,4,5,[12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%